PENGEMBANGAN E-LKPD BERBASIS ETNOMATEMATIKA BERBANTUAN LIVE WORKSHEET MATERI KERAGAMAN BUDAYA KELAS IV SDN 1 SEDAYU WONOSOBO - Enik Wahyuningsih; Sutrisno Wibowo (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The research method that will be used in this study is the Research and Development (RnD) method. The research and development design in this study uses the Thiagarajan model, which is also known as the 4D model that is modified into 3D, namely define, design, and development. The data collection tools used were tests of mathematical understanding ability, validation sheets, and teacher response questionnaires. The product trial subjects in this study were 28 class IV A students at SD Negeri 1 Sedayu. The purpose of this research is to develop Ethnomatematics-based E-LKPD Live Worksheets for Mathematical Understanding Ability in Opportunity Materials in Class IV SD Negeri 1 Sedayu as seen from the level of validity, effectiveness and practicality The results of the average percentage validation obtained is 94.44% with very valid criteria. For the results of the teacher's response questionnaire, it obtained a score percentage of 96.47% with very practical criteria, so the developed E-LKPD can be used as teaching material with a little revision. Classical learning mastery can be achieved if it fulfills 75% with the student's score having to be greater than or equal to 75. The results of the test students get a percentage score of 85.72% with very effective criteria. From these results it can be concluded that the developed E-LKPD is feasible to use.